Influence of Donor-Acceptor Interactions on MLCT Hole Reconfiguration in Ru(bpy) - Cotic, Agustina; Heinemann, Frank Wilhelm; Slep, Leonardo D.; Cadranel, Alejandro (ChemPhysChem)
In MLCT chromophores, internal conversion (IC) in the form of hole reconfiguration pathways (HR) is a major source of dissipation of the absorbed photon energy. Therefore, it is desirable to minimize their impact in energy conversion schemes by slowing them down. According to previous findings on Ru(bpy) chromophores, donor-acceptor interactions between the Ru ion and the ligand scaffold might allow to control HR/IC rates. Here, a series of [Ru(tpm)(bpy)(R-py)]2+ chromophores, where tpm is tris(1-pyrazolyl)methane, bpy is 2,2’-bipyridine and R-py is a 4-substituted pyridine, were prepared and fully characterized employing electrochemistry, spectroelectrochemistry, steady-state absorption/emission spectroscopy and electronic structure computations based on DFT/TD-DFT. Their excited-state decay was monitored using nanosecond and femtosecond transient absorption spectroscopy. HR/IC lifetimes as slow as 568 ps were obtained in DMSO at room temperature, twice as slow as in the reference species [Ru(tpm)(bpy)(NCS)]+.
CRIS-Team Scopus Importer:2024-06-14
Keywords: artificial photosynthesis; dissipation; energy conversion; internal conversion; ultrafast spectroscopy